HUBUNGAN MOTIVASI BELAJAR DAN PERILAKU HIDUP SEHAT DENGAN PRESTASI BELAJAR KEJURUAN OTOMOTIF KELAS XI PROGRAM KEAHLIAN TEKNIK OTOMOTIF SMK MUHAMMADIYAH IMOGIRI BANTUL TAHUN AJARAN 2014/2015 - Syahrul Falah; Suparmin Suparmin (Universitas Sarjanawiyata Tamansiswa, 2016)
The study aimed to describe (1) correlation between learning motivation with learning achievement of automotive vocational; (2) correlation between healthy live attitude with learning achievement of automotive vocational; and (3) correlation between learning motivation and healthy live attitudewith learning achievement of automotive vocational. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression. This study shows that there was a positive and significant correlation between learning motivation with learning achievement of automotive vocational; (2) there was a positive and significant correlation between healthy live attitude with learning achievement of automotive vocational; and (3) there was a positive and significant correlation between learning motivation and healthy live attitude with learning achievement of automotive vocational.